2003
DOI: 10.1034/j.1600-0447.2003.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of manic symptoms during a depressive episode and unipolar ‘depressive mixed state’ as bipolar spectrum

Abstract: Depressive mixed state is frequent, particular in bipolar depressives. Unipolar depressives with DMS may be better classified into bipolar spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
109
2
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 40 publications
12
109
2
2
Order By: Relevance
“…Strakowski 25 and Sato 63 also found an association between suicidality and mixed mania. Johnson 32 found that mixed state was a predictor of future suicidal acts.…”
Section: 23mentioning
confidence: 92%
“…Strakowski 25 and Sato 63 also found an association between suicidality and mixed mania. Johnson 32 found that mixed state was a predictor of future suicidal acts.…”
Section: 23mentioning
confidence: 92%
“…He reported that the presence of racing thoughts has a sensitivity of 88% and a specificity of 54.6%; a positive predictive value of 66.1% and a negative predictive value of 82% for the diagnostic of depressive mixed state, as defined by the association of a major depressive episode with three hypomanic symptoms . Most common manic symptoms found in unipolar depression include psychomotor agitation, irritability, and distractibility (Serretti and Olgiati, 2005), often joined by racing thoughts (Akiskal et al, 2005;Benazzi and Akiskal, 2001;Sato et al, 2003). We see that racing thoughts are not uncommon in depression, and usually associated with others symptoms of "agitation".…”
Section: Association Of Racing/crowded Thoughts With Other Affective mentioning
confidence: 97%
“…Interestingly, however, this study reported a very high prevalence of "thoughts confused" that could be related to crowded thoughts. A prevalence of 6% is reported in another study using the AMDP system and looking at racing thoughts in unipolar depressed patients, with this frequency increasing respectively to 12 and 14% in bipolar II and bipolar I depressed patients (Sato et al, 2003). A very low rate of "thoughts racing" was found in unipolar MDD inpatients (1 out of 372) by another study using some items of the OPCRIT (operational criteria for psychotic illness checklist: (Serretti and Olgiati, 2005)).…”
Section: Prevalence Of Racing/crowded Thoughts In Mood Disordersmentioning
confidence: 99%
“…Increased goal-directed activity and decreased need for sleep have been found to be uncommon, while elevated or expansive mood, inflated self-esteem or grandiosity, and excessive involvement in pleasurable activities have been reported to be very rare or absent. 4,5 This condition has been found to occur in a proportion of patients with unipolar major depression ranging from 7% to 60%, and to be associated with an earlier onset than "pure" major depression; a more common family history of bipolar disorder; a higher prevalence of suicidal behavior, psychiatric comorbidity, traumatic brain injury, and alcohol abuse; a more frequent unipolar to bipolar switch; and a poorer response to antidepressants. 6,7 The DSM-5 has acknowledged the occurrence of this condition by introducing a specifier "with mixed features" to the diagnosis of major depressive disorder.…”
Section: "Mixed" Depression: Drawbacks Of Dsm-5 (And Other) Polythetimentioning
confidence: 99%